KÓP KRITERIYALÍ JANTASÍW TIYKARÍNDA ELEKTRON TÁLIM RESURSLARÍN BAHALAW PROCESIN MODELLESTIRIW - Baymurzaeva, A.A. (SCIENCE and SOCIETY, 2025)
This article analyzes the process of evaluating electronic learning resources using a multi-criteria approach and models it through a Sequence Diagram. The proposed framework provides a methodological basis for systematic quality assessment and effective resource management.